PERAN KPU SUMBA BARAT DAYA DALAM MENINGKATKAN PARTISIPASI PEMILIH PEMULA PADA PEMILU TAHUN 2024 DI KECAMATAN KOTA TAMBOLAKA BERDASARKAN PKPU NOMOR 10 TAHUN 2018 - Mira Dida, Isa Mesakh; Monteiro, Josef M; Lawung, Mario A (Petitum Law Journal, 2025)
The purpose of this study is to examine the General Elections Commission's function of Southwest Sumba Regency in boosting involvement of first-time voters in the 2024 General Election in Kota Tambolaka District. As first-time voters, particularly those from Generation Z aged 17–21, play a strategic role in shaping the future of democracy in Indonesia, their active participation is crucial. However, low political awareness and limited access to voter education pose challenges. Using a qualitative legal research approach with empirical data collection methods, this study identifies the programs and strategies implemented by General Elections Commission's, such as voter education, school outreach, and social media campaigns. The findings reveal that although several efforts have been made, obstacles remain, including inadequate understanding of electoral processes among young voters and limited engagement strategies tailored to their interests. The study concludes that strengthening voter education and collaboration with educational institutions are essential to foster meaningful political participation among first-time voters.